Co-infections of ectoparasite species in synanthropic rodents of western Sarawak, Malaysian Borneo - Ng, Y. L; Hamdan, N.E.S; Andrew Alek, Tuen; Mohd Azlan, Jayasilan; Chong, Y. L. (Malaysian Society of Parasitology and Tropical Medicine, 2017)
Little is known regarding infestation of ectoparasites in synanthropic rodents in Sarawak, Malaysia. A total of 44 rodents from three species (Rattus rattus, Rattus tiomanicus and Sundamys muelleri) were trapped from four residential areas in western Sarawak, Malaysia, for ectoparasites screening. A total of 117 ectoparasites from three hard tick species (Ixodes granulatus, Haemaphysalis sp. 1, Haemaphysalis sp. 2), three mesostigmatid mite species (Laelaps echidninus, Laelaps sedlaceki, and Laelaps nuttalli), one trombiculid mite (chigger species), and one louse species (Hoplopleura sp.), were recovered from 32 infected rodents (72.73% infestation). Infestations by multiple ectoparasite species on the same rodent individuals were recorded in R. rattus and R. tiomanicus (28.1%, n=9) in this study, while Sundamys muelleri was only infested with L. echidninus. One R. rattus individual was co-infected with ticks, louse, and mesostigmatid mite. L. echidninus was the generalist ectoparasite species that infected all three rodent species in three of the residential areas studied. Ectoparasite species diversity was significantly different among four residential areas based on Shannon index and diversity t-test (p-value <0.05). This study provides the first record of the association of synanthropic rodents with multiple ectoparasite infections in residential areas of western Sarawak, Malaysia.